Reliability of transversus abdominis thickness and inter-recti distance during forced expiration with limb adduction in primiparous women following vaginal delivery - Patricia Pérez-Pascual; Elena Vegas-Sánchez; Sandra Ortiz-Barahona; Guillermo García-Pérez-de-Sevilla; María García-Arrabé; Gonzalo Jaén-Crespo; Ángel González-de-la-Flor (BMC Pregnancy and Childbirth, 2025)
Abstract Introduction The postpartum period involves significant biomechanical changes that impact maternal health, particularly in the activation of the transversus abdominis (TrA) and the inter-recti distance (IRD), which may contribute to lumbo-pelvic pathologies. While lumbopelvic exercises are beneficial, it remains unclear whether upper or lower limb adduction combined with forced expiration is more effective in activating the TrA. Therefore, the primary objective of this study is to analyze changes in TrA thickness and IRD during four conditions. The secondary objective is to evaluate the intra-observer reliability of these ultrasound measurements. Methods This cross-sectional study, conducted with a sample of 32 participants, assessed TrA thickness (primary outcome) and IRD (secondary outcome), quantified under four conditions: (1) resting position, (2) forced expiration, (3) forced expiration with upper limb adduction, and (4) forced expiration with lower limb adduction. Differences between the four conditions were analyzed using repeated measures ANOVA. The intra-observer reliability of these measurements was evaluated using intraclass correlation coefficients (ICC). Results A total of 32 primiparous women between January and April 2024 were included in this study with a mean postpartum period of 9 ± 2.33. Significant variations in TrA thickness were observed across conditions (p < 0.001). Differences were noted between resting and forced expiration (MD = -0.17, p < 0.001) and forced expiration with lower limb adduction (MD = -0.20, p < 0.001) on both sides. For the right TrA, forced expiration differed from upper limb adduction (MD = -0.04, p = 0.007), while no difference was found between upper and lower limb adduction (MD = -0.005, p > 0.05). For IRD, no significant differences were detected across conditions, including resting and lower limb adduction (MD = -0.018, p = 0.727). Excellent intra-examiner reliability was demonstrated for all ultrasound measurements (ICC (1,3) 0.92–0.99). Conclusions There were no significant differences in TrA thickness between forced expiration isolated and when combined with adduction exercises. The high ICC values confirm the robustness of ultrasound measurements for TrA and IRD, highlighting the potential for future research in postpartum rehabilitation strategies.